Predictors of Endovascular Treatment Procedural Complications in Acute Ischemic Stroke: A Single-Center Cohort Study - Maslias, E.; Puccinelli, F.; Nannoni, S.; Hajdu, S.D.; Bartolini, B.; Ricciardi, F.; Dunet, V.; Maeder, P.; Strambo, D.; Saliou, G.; Michel, P. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Procedural complications occur in 4%–29% of endovascular treatments in acute ischemic stroke. However, little is known about their predictors and clinical impact in the real world. We aimed to investigate the frequency and clinical impact of procedural complications of endovascular treatment and identify associated risk factors.MATERIALS AND METHODS: From 2015–2019, we retrospectively reviewed all patients with acute ischemic stroke receiving endovascular treatment within 24 hours included in the Acute STroke Registry and Analysis of Lausanne. We identified patients having an endovascular treatment procedural complication (local access complication, arterial perforation, dissection or vasospasm, and embolization in a previously nonischemic territory) and performed logistic regression analyses to identify associated predictors. We also correlated procedural complications with long-term clinical outcome.RESULTS: Of the 684 consecutive patients receiving endovascular treatment, 113 (16.5%) had at least 1 procedural complication. The most powerful predictors were groin puncture off-hours (OR = 2.24), treatment of 2 arterial sites (OR = 2.71), and active smoking (OR = 1.93). Patients with a complication had a significantly less favorable short-term clinical outcome (Δ-NIHSS score of −2.2 versus −4.33, P-value adjusted < .001), but a similar long-term clinical outcome (mRS at 3 months = 3 versus 2, P-value adjusted = .272).CONCLUSIONS: Procedural complications are quite common in endovascular treatment and lead to a less favorable short-term but similar long-term outcome. Their association with treatment off-hours and at 2 arterial sites requires particular attention in these situations to optimize the overall benefit of endovascular treatment.AISacute ischemic strokeEVTendovascular treatment